Performance of Vivaldi Antennas in Reflector Feed Applications - Tokan, Nurhan T. (APPLIED COMPUTATIONAL ELECTROMAGNETICS SOC, 2013)
When a wideband antenna is to be used as a reflector feed, the phase center variation with frequency introduces an error on the phase of the primary field impinging on the reflector surface. This is because the antenna phase center will be coincident with the focus only at one particular frequency and displacement at other frequencies, which will result as the phase error losses due to axial defocusing. Tapered slot antennas are the most utilized antennas in ultra wide band (UWB) high-performance applications. In this work, performance of the UWB Vivaldi antennas (exponentially tapered slot antennas) in reflector feed applications is investigated. A long Vivaldi is designed, manufactured, and its phase center movement with frequency is measured. The correspondent phase error loss is estimated.
Keywords: Astigmatism; axial defocusing; phase error loss; reflector feed; ultra wide band; Vivaldi antenna; Engineering; Telecommunications